1993
DOI: 10.1007/bf01195348
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy for recurrent adeno- and adenoidcystic carcinomas in the head and neck

Abstract: We have investigated the effectiveness of chemotherapy for patients with recurrent adeno- and adenoidcystic carcinomas in the head and neck. Fourteen cases received a monthly combination chemotherapy regimen of cyclophosphamide, pirarubicin and cisplatin (CAP therapy). A response rate of 36% (5/14) was achieved. There was one complete response and four partial responses. The median duration of response was 37 months in the complete response case and 16 months (range, 6 to 20) in the partial response cases. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…The diffi culty in treating recurrent ACC involving the skull base has led investigators to consider additional treatments beyond conventional surgery and radiation therapy. However, chemotherapy is largely ineffective in this setting [2,4] . Tsukuda et al [4] reported that the response rate of IAP (cyclophosphamide, pirarubicin and cisplatin) therapy was only 33% in 6 recurrent ACC in the head and neck.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The diffi culty in treating recurrent ACC involving the skull base has led investigators to consider additional treatments beyond conventional surgery and radiation therapy. However, chemotherapy is largely ineffective in this setting [2,4] . Tsukuda et al [4] reported that the response rate of IAP (cyclophosphamide, pirarubicin and cisplatin) therapy was only 33% in 6 recurrent ACC in the head and neck.…”
Section: Discussionmentioning
confidence: 99%
“…However, chemotherapy is largely ineffective in this setting [2,4] . Tsukuda et al [4] reported that the response rate of IAP (cyclophosphamide, pirarubicin and cisplatin) therapy was only 33% in 6 recurrent ACC in the head and neck. SRS for various brain tumor histologies has been investigated by a number of institutions [5,6] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of therapy was based on several small phase ii studies identifying that combination as active in the treatment of malignant salivary gland tumours, although with efficacy varying by histologic subtype [10][11][12] . Newer combinations such as carboplatin-paclitaxel or cisplatin-gemcitabine have demonstrated moderate activity in small trials involving salivary gland tumours with a mix of histologies 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Schramm and colleagues 35 used cisplatin as a single agent in a pilot study and reported an overall response rate of 70%. Two other studies of recurrent salivary gland epithelial tumors revealed response rates of 36% 36 (cisplatin combined with cyclophosphamide and pirarubicin) and 35% 37 (cisplatin combined with doxorubicin and fluorouracil). These response rates were achieved despite the fact that the patients had a poor prognosis due to advanced tumor involvement.…”
mentioning
confidence: 99%